Effect of Service Performance on Community Satisfaction Olibu Village, District of Paguyaman Pantai, Boalemo Regency - Wirson D. Sawal; Moh. Sapril T Mohu; Maman Musa (Journal of Economic, Business, and Administration (JEBA), 2021)
The purpose of this study was to determine:1) the still slow service of village government officials in serving the communityl; 2) the attitude of village officials who were less friendly in serving the community, 3) village government officials were still not on time in serving the community. Survey research with a quantitative approach and data obtained through observation data collection techniques, questionnaires, documentation for further processing using correlation and simple regression. The results showed that the results of the correlation analysis with the Pearson product moment (PPM) formula obtained the value of r = 0.399. This means that service performance has a very close relationship with community satisfaction. Meanwhile, from the results of the significance test by comparing the probability value of 0.05 with the sig value, it is known that the probability value is greater than the sig value (0.05> 0.001), this indicates that there is a significant relationship between Service Performance. and Community Satisfaction. Furthermore, from the results of linear regression testing, the correlation coefficient Rsquare = (0.160) was obtained. This shows that (Y) is influenced or contributed by (X) of 16.0% and the remaining 84.0% is influenced by other factors or variables. The results of linear regression testing also obtained a regression equation y ̂ = 20.242 + 0.399x. Therefore, every 1 unit addition to the service quality variable, will increase the reality by 0.399 and vice versa. Thus, it can be stated that any increase or decrease in the independent variable (X) will result in an increase/decrease in the dependent variable (Y). This shows that the researcher's hypothesis is proven and acceptable.